Multiple intestinal lymphangiomas with episodic hemorrhage requiring partial laparoscopic resection: a case report - Hiroka Kondo; Takeshi Ohki; Shimpei Ogawa; Teppei Omori; Hiromi Onizuka; Yoji Nagashima; Shigeki Yamaguchi (Surgical Case Reports)
Abstract Background Lymphangioma is a non-epithelial tumor marked by aggregates of abnormally dilated lymphatics. Mesenteric occurrences account for < 1% of all cases, and < 0.05% involve the gastrointestinal tract. Most are confined to children, rarely affecting adults. Case presentation Herein, we describe an elderly Japanese woman with anemia, hypoalbuminemia, and episodic bleeding due to multiple intestinal lymphangiomas. Abdominal computed tomography revealed multiple low-density defects of mesentery, with areas of intermediate (T1 images) or high (T2 images) signal intensity similarly dispersed in magnetic resonance scanning sequences. Single-balloon enteroscopy was undertaken, enabling identification and tattooing of a small intestinal bleeding source. Laparoscopy-assisted resection at this site served to control related hemorrhage, removing a histologically confirmed hemolymphangioma. Having recovered uneventfully, the patient remained stable 2 months postoperatively. Conclusions Although rare in adults, mesenteric or gastrointestinal lymphangiomas must be considered in a setting of anemia and hypoalbuminemia. Complete resection is advantageous to improve patient symptoms, but limited resection of multiple lesions may be equally effective.